Counterfactual History and Diasporic Identity in Philip Roth’s The Plot against America - Raluca Moldovan (Caietele Echinox, 2023)
The Plot against America, a 2004 novel by acclaimed American author Philip Roth, starts out from a counterfactual premise, i.e., that aviation pioneer Charles Lindbergh defeated Franklin D. Roosevelt in the 1940 election, running on an isolationist platform summarised in the slogan “America first!” The novel is a masterful exploration of trauma and the perception of history viewed through the eyes of a young boy, the author’s alter ego, Philip, who is also the narrator, and who sees his family and others around him question their place in society and their identity as American Jews in a world swiftly turning against them.